ASENTAMIENTOS CERRADOS PREHISPÁNICOS EN YANAPIRURO E ICHUBAMBA, CHIARA, AYACUCHO - Carhuas Tenorio, Héctor (2017)
The present work is the result of the archaeological investigations carried out in the rural community of San Martin de Yanapiruro and Ichubamba, in the jurisdiction of the district of Chiara, province of Huamanga, region Ayacucho. It basically contains an informative value that gives to the community in general new records of closed settlements such as caves and rocky coats, associated with pictographs, lithic, ceramic and architecture. Based on these evidences we intend to reconstruct the prehispanic history of a high Andean population, in Relation to the surrounding environment.